Leadership Strategies in Developing the Quality of Education at Al-Irsyad Kademanan Bondowoso Senior High School (MA) for the 2024-2025 Academic Year - Novani Elika Saputri Vani; Akhmadi; Rifa’i (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Leadership strategies and educational quality development are two interconnected elements in creating a quality education system. Effective leadership can be the main driver in ensuring that education continues to evolve and meet the expected quality standards. This research aims to: (1) describe leadership strategy planning in developing the quality of education at MA Al-Irsyad Kademangan Bondowoso, (2) describe the implementation of leadership strategies in developing the quality of education at MA Al-Irsyad Kademangan Bondowoso, (3) describe the evaluation of leadership strategies in developing the quality of education at MA Al-Irsyad Kademangan Bondowoso. The research method used is a qualitative approach that generates naturalistic data in the form of natural explanations. Data collection methods include observation, interviews, and documentation. Data analysis methods are interactive, using Miles and Huberman's approach of data reduction, data presentation, and conclusion drawing. The research subjects are the principal, the vice-principal for curriculum, and the teachers. The results of this study indicate that: (1) the strategic leadership planning in developing the quality of education at MA Al-Irsyad Kademangan Bondowoso is first, the existence of a working meeting team, and second, the existence of a curriculum development team. (2) the implementation of strategic leadership in developing the quality of education at MA Al-Irsyad Kademangan Bondowoso includes the implementation of planned programs and extracurricular activities, as well as class management mentoring training, teaching modules prepared by each educator, learning innovation training, and psychological tests for teaching and administrative staff, and talk show activities. (3) the evaluation of strategic leadership in developing the quality of education at MA Al-Irsyad Kademangan Bondowoso includes self and madrasah evaluation, and learning evaluation